Jón Hilmar Jónsson. 1994. Orðastaður. Orðabók um íslenska málnotkun. Reykjavík: Mál og menning. - Simensen, Erik (LexicoNordica, 1995)
Jón Hilmar Jónsson: Orðastaður. Orðbók um íslenska malnotkun. Mal og menning. Reykjavik 1994. 698 s. This dictionary is especially designed to show the combinatory properties of words in Icelandic, concentrating on the three big word classes: nouns, verbs and adjectives. The author describes their syntactical use and collocations and their ability to enter into compounds. On the whole, the dictionary is highly commendable. The present reviewer mainly objects to its use of boxes, which are filled with heterogeneous kinds of comment, whereas different types of information are otherwise given distinct graphic expressions.